Rejs . The Cruise - Piwowski, Marek (Zespol Tor ; Best Film, 1970)
Duration: 01:06:00 "The Cruise" is the mother of all cult films in Polish cinematography, yet a strange one with its incredibly banal plot. A stowaway sneaks aboard a ship departing on a cruise down the Vistula River. The captain takes him for a Communist Party cultural coordinator and the intruder gladly adapts to his new role, immediately setting to work to manipulate the passengers and crew into silly and vaguely humiliating games. They quickly formed “cruise committee” and organize a birthday party for the captain. The plot is overshadowed by the dialogues between the cruise participants, resting, sunbathing and chatting. The dialogues initially seem accidental, yet as the film unfolds they reveal their paradoxical inner logic and prove justifiable, but perhaps not easily understandable for a non-polish audience. They refer to the Polish reality of the late 60s, disclosing its absurdities. Shot in quasi-documentary style, "The Cruise" features a handful of professional actors. Most of the cast are carefully selected amateurs who follow the script rather loosely and were provoked rather than directed by Piwowski and Glowacki – a writer and a co-author of the screenplay.